COVID-19 and its impact on cardiology service - Harky, Amer; Chor, Cheryl Yan Ting; Khare, Yuti (Acta Biomedica Atenei Parmensis, 2020)
COVID-19 has impacted the primary management of cardiac conditions, decreasing the number of interventions of coronary diseases. Elective coronary treatments and imaging have been largely cancelled across the world to make way for increased resources for COVID-19 patients. The impact on these cardiac patients during these times may be drastic. The number of hospital patients presenting with coronary symptoms during the outbreak has also decreased internationally. In this review, we discuss how COVID-19 has affected primary cardiac intervention globally and our service, possible reasons why, and how morbidity rates can be reduced by introducing scoring systems and telemedicine.